2022
DOI: 10.1186/s13019-022-01920-9
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of two surgical approaches for acute type A aortic dissection: hybrid debranching versus total arch replacement

Abstract: Background The goal of this study was to determine the clinical outcomes of total arch replacement with frozen elephant trunk surgery and hybrid debranching surgery for acute type A aortic dissection patients. Methods From January 2017 to December 2019, the clinical data of acute type A aortic dissection patients were retrospectively collected and analyzed. There were 142 patients underwent total arch replacement with frozen elephant trunk surgery … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 17 publications
1
6
0
Order By: Relevance
“…The current study explored the two-stage HAR procedure for high-risk elderly a-TAAD patients based on previous studies and achieved good results. CPB, ACC, HCA, mechanical ventilation, ICU stay and hospital stay times were shorter and the complications of acute liver injury, AKI and pulmonary infection were lower in the two-stage HAR group than that in the TAR with FET group, which were consistent with previous one-stage HAR studies 8 10 .…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…The current study explored the two-stage HAR procedure for high-risk elderly a-TAAD patients based on previous studies and achieved good results. CPB, ACC, HCA, mechanical ventilation, ICU stay and hospital stay times were shorter and the complications of acute liver injury, AKI and pulmonary infection were lower in the two-stage HAR group than that in the TAR with FET group, which were consistent with previous one-stage HAR studies 8 10 .…”
Section: Discussionsupporting
confidence: 90%
“…HAR combines open surgical debranching with TEVAR, preventing HCA and simplifying the operation, thereby reducing mortality 21 . Recently, the HAR technique has been widely employed in the treatment of a-TAAD, and achieved good short- and medium-term results 8 10 . A recent meta-analysis of 1305 patients from 11 studies compared the results of type II HAR and TAR with FET.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The result is a significant shortening of the arrest, clamp, and operation room times with the potential for less neurological and other complications. 62 Besides the publications in 2022 that supported the concept that arch replacement potentially including elephant trunks may be an option in experienced hands with improved long-term survival, 63 other publications addressed the elevated risk of octogenarians with type A dissections 64 and the need for individual patient selection. 65 An impressive study was published from Paris and Bologna.…”
Section: Glimpse Into Surgery Of the Aorta And For Terminal Heart Fai...mentioning
confidence: 99%
“…(19,20) Hybrid EAR with a frozen elephant trunk (FET) has become a popular and promising option for patients in need of aortic arch repair. (17,21,22) Single-center studies have indicated long-term benefits of this approach without increasing perioperative risks. The evidence supports the use of hybrid EAR as a diverse and effective alternative to traditional arch replacements.…”
Section: Introductionmentioning
confidence: 99%